Pengaruh Pemahaman Teknologi Informasi, Value for Money, dan Pengendalian Internal Terhadap Good Coorporate Governance pada Badan Pengelolaan Keuangan dan Aset Daerah Kota Metro - Khairannisa, Khairannisa; Zanaria, Yulita; Padwa Sari, Gustin (Expensive: Jurnal Akuntansi dan Keuangan, 2024)
This study aims to examine the effect of Understanding Information Technology, Value for Money and Internal Control on Good Corporate Governance at the Regional Financial and Asset Management Agency in Metro City. This study uses Agency Theory (Agency Theory). The method in this study uses a quantitative descriptive method using a Likert scale. The number of samples used in this study were 53 respondents with the criteria of Metro City BPKAD employees. The results of the study show that: (1) Understanding of Information Technology has a positive effect on Good Corporate Governance. (2) The understanding of Value for Money has a negative effect on Good Corporate Governance. (3) the influence of Understanding of Internal Control has a positive effect on Good Corporate Governance. (4) Together the variables of Information Technology, Value for Money and Internal Control simultaneously have a positive effect on Good Corporate Governance at the Regional Financial and Asset Management Agency for Metro City